Association between diabetes mellitus and central arterial stiffness in elderly patients with systemic arterial hypertension - Romário Divino Vilarinho Galvão; Cristiane de Sousa Pereira; Ercilhana Gonçalves Batista Freitas; Damianna R. A. R. Teixeira Lima; Walkiria Almeida Martins Santos; Denis Fabiano Souza; Quintiliano Siqueira Schroden Nomelini; Sebastião Rodrigues Ferreira-Filho (Clinical and Experimental Hypertension, 2020)
Background Aging increases the risk of chronic diseases, especially cardiovascular diseases, leading to changes in cardiovascular anatomy and physiology even in the absence of other comorbidities. Numerous cardiovascular risk factors (CVRFs), such as diabetes mellitus (DM) and systemic arterial hypertension (SAH), can modify the functional and structural properties of large vessels, increasing arterial stiffness. Objective To determine whether elderly patients with hypertension with DM have greater central arterial stiffness than elderly patients with SAH without DM. Methods The Study of Pulse Wave Velocity in the Elderly in an Urban Area in Brazil (EVOPIU) included 1,192 patients aged ≥ 60 years who underwent applanation tonometry (AT) to evaluate carotid-femoral pulse wave velocity (cfPWV). From this database, 1,133 patients were selected from 6 groups: NDN (nondiabetic normotensives; n: 127); DN (diabetic normotensives; n: 64); NDCH (nondiabetic controlled hypertensives; n: 168); DCH (diabetic controlled hypertensives; n: 275); NDH (nondiabetic hypertensives; n: 217) and DH (diabetic hypertensives; n: 282). All groups underwent AT to obtain cfPWV and central and peripheral arterial pressures. Results The pulse wave velocities found were as follows: NDN vs DN (8.9 ± 0.2 m/s vs 9.4 ± 0.2; P = .103); NDCH vs DCH (9.0 ± 0.2 m/s vs. 9.6 ± 0.1 m/s; P= .04) and NDH vs DH (9.2 ± 0.1 m/s vs. 9.6 ± 0.1 m/s; P= .045). When the diabetic groups were compared, there were no differences in cfPWV values, and the same occurred when the nondiabetic groups were compared. Conclusions Elderly patients with diabetes and hypertension have greater central arterial stiffness than patients without diabetes and hypertension, regardless of systemic blood pressure control. The central arterial stiffness caused by vascular aging seems to be a common factor among all the studied groups.